ERADICATION OF POVERTY âSEKOLAH PEMULUNG RINTISAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH)â - Amalia, Rezky; Merdekawaty, Dian (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The poverty happens because of the accumulation of the variety of issues and involves many aspects. Not merely in the economic aspect but the Poverty also associated with social, political, cultural, human resources (education) and various other aspects. The thing that happened in Indonesia is the existence of vicious circle of poverty, which is formed by the concatenation of problems and gave an effect to the other things. The vicious cirle of poverty lead to circumstances in which a country will be remain poor and will experience many difficulties to achieve a higher level of development. The vicious circle impress as though the eradication of poverty is very difficult to get. The problems are always intertwined and just spin in a circle without a clear solver. So the concrete program called pioneering school of MSMB (Micro, Small and Medium Business) could be a solution. This program has been implemented by using the set of methods, both the pre-execution method and program execution method that packed with an interesting concept for children in the games, visual drawing, etc. From this program, the offspring of scavengers nurtured into competitive individuals with speech capabilities entrepreneurship and get the capability to produce the products that can compete in the market when they become an adult, they could use their provision for their future. So they do not just pass the science scavenged from their parents, but will be a pioneer breaker circle of familyâs poverty trap. Until eventually the concept of eradication of poverty as the mandate of the Preamble of the Constitution of 1945 could soon become a reality in the social life.Keywords: School of scavenger, Eradication of poverty, MSMB (Micro, Small and Medium Business)